DC-CIK as a widely applicable cancer immunotherapy. (2nd June 2020) - Wang, Shuo; Wang, Xiaoli; Zhou, Xinna; Lyerly, Herbert Kim; Morse, Michael A.; Ren, Jun
ABSTRACT: Introduction : Immunotherapy is now a standard treatment for many malignancies. Although immune checkpoint inhibition has demonstrated substantial efficacy by enhancing T cell activation and function in the tumor microenvironment, adoptive transfer of T and NK cell products promises to provide activated cells capable of immediate and direct tumor destruction. A widely applicable, non-MHC dependent, cellular therapy, consisting of in vitro generated dendritic cells (DC) combined with cytokine-induced killer cells (CIK), is highly efficient to produce from individual patients and has demonstrated safety and efficacy alone or with chemotherapy. Areas covered : We summarize the clinical data from studies of DC-CIK and discuss future research directions. Expert opinion : Patients with a wide variety of tumor types who have received DC-CIK therapy may experience clinical responses. This versatile therapy synergizes with other anti-cancer therapies including chemotherapy and immunotherapy.